Incidence and predictors of chronic kidney disease among patients with diabetes treated at governmental hospitals of Harari Region, eastern Ethiopia, 2022 - Abera Cheru; Dumessa Edessa; Lemma Demissie Regassa; Tesfaye Gobena (Frontiers Media S.A., 2024)
BackgroundChronic kidney disease (CKD) is the leading cause of morbidity and mortality in diabetic patients. However, limited evidence is available about its incidence and predictors in Ethiopia, specifically in the Harari region.MethodsA retrospective follow-up study was conducted among 520 diabetes patients who followed their treatment at governmental hospitals in the Harari region between 1 September 2012, and 30 May 2022. The risk of developing CKD was calculated with a 95% CI, and the risk was stratified by type of diabetes mellitus. Predictors of CKD were determined using the Gompertz regression model with the baseline Cox model.ResultsData from 494 patients were included in the final analysis with 26 (5%) excluded. A total of 51 patients (10.32%) developed CKD over the 10-year follow-up period with an incidence rate of 2.16 cases (95% CI 1.64-2.84) per 100 person-years of observation. The risk of CKD was increased by three times (AHR: 3.09, 45 95% CI: 1.56, 6.14) among patients older than 60 years and by more than three times (AHR: 3.53, 95% CI: 1.43, 8.71) among patients with diabetes mellitus for longer than 5 years of stay with the diabetes mellitus. Moreover, the risk of CKD was increased four-fold among patients with high-density lipoprotein cholesterol (HDL-C) levels <40 mg/dL (AHR: 3.84, 95% CI, 1.80-8.18) and those with positive baseline proteinuria (AHR: 3.77, 95% CI: 1.43-8.71).ConclusionWe found that one in ten diabetic patients had developed CKD within 10 years of the diabetes mellitus diagnosis. Advanced age, longer duration of diabetes, lower baseline HDL-C level, and proteinuria had increased the hazards of developing CKD. We recommend a more focused follow-up of older adult patients with advanced disease status at baseline for optimal control of diabetes mellitus that prevents its furthering to CKD.